Pengaruh Alquran Dan Hadits Terhadap Bahasa Arab - Musgamy, Awaliyah (Al-Hikmah Journal for Religious Studies, 2014)
Alquran is an eternal miracle which is able to become Balagah experts speechless who wants to ignore the guideline of Allah Swt by making great poem which Â isÂ  created by themselves. The habitual and Arabian tradition who always vied in versifies the great poem. It caused Al-Qurâan be accepted and be able to developed atop, it is including of words transformation, structural and its style of language. Allah Swt decrees through His messengers with the language clearly and wisely. No one speaks fluently except His prophets. Allah Swt gives them spoken style and teaches them languages and Arabian dialects. Even though, His prophet has not yet communicated in social life with them. Because Allah Â Swt wants them become teacher, guide, and Imam Â for Â all mankind. The style of prophets spoken is balagah (brief, solid, interesting). His style spoken of beautifulness is the second place after al-Qurâan itself. His superiority cannot be defeated by the great poet or the great orator who ever exist. The spoken is clear, beautiful, and calm based the situation and condition, so it is euphony and digestible for All Muslim who want to learn Â about Islam fundamental and of course there is no other choices Â except learning Arabic. Therefore, Allah Swt always keeps Arabic from extinct.